Studi Tentang Kesejahteraan Kelompok Tani Kelapa Sawit di Desa Kerta Bumi Kecamatan Kuaro Kabupaten Paser (Implementasi Peraturan Daerah Kabupaten Paser Nomor 12 Tahun 2019 Tentang Kelembagaan Petani) - Arvin Sulistiyawan; Heryono Susilo Utomo; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This study aims to analyze and describe the Welfare of Palm Oil Farming Groups in Kerta Bumi Village, Kuaro District, Paser Regency by outlining the Implementation of Regional Regulation No. 12 of 2019 concerning Farmer Institutions as seen through the Empowerment of Farmer Groups in the form of Farmer Group Independence in the form of Farmer Independence, Ability to innovate , also Welfare income level. This research was conducted at the Office of Plantation and Animal Husbandry, Paser Regency and the Kerta Bumi Village Office, Kuaro District, Paser Regency. This type of research is descriptive qualitative. The results of the study show that regarding the welfare of farmer groups by looking at the implementation of Regional Regulation No. 12 of 2019 concerning Farmer Institutions that the independence of oil palm farmer groups has been felt by oil palm farmers by working independently or independently from farmer group membership. Second, the ability of oil palm farmer groups has been able to innovate in various fields (technical, economic and social) by developing renewable techniques, improving the economic and social fields. Third, the income and welfare of the oil palm farmer groups has increased quite well because the commodity of palm oil has experienced an increase in selling value. Fourth, monitoring is carried out by the government in the form of outreach and counseling related to oil palm and other programs. Fifth, the government has so far never done an evaluation so that oil palm farmers have never received it due to budget constraints.